1995
DOI: 10.1002/app.1995.070550210
|View full text |Cite
|
Sign up to set email alerts
|

Graft copolymerization of dimethylacrylamide onto AFLAS

Abstract: SYNOPSISThe method of irradiation grafting of DMAA onto AFLAS (alternating copolymer of tetrafluoroethylene and propylene) films was studied. The effect of the solvent on the grafting yield was determined. As a result, it might be important to evaluate the blood compatibility of the films already grafted by using an in uitro test. Benzene tests seem to be the most adequate for copolymerization. Grafting yield was better in the monomer 40-60% concentration range. The degree of grafting increases proportionally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Thus, modified polymers having polar groups, called as compatibilizers or interfacial agents must be introduced in nanocomposite formulations to enhance the extent of intercalation as well as dispersion of organoclay in polyolefin matrix. In most research works carried out on polypropylene/organoclay nanocomposites prepared by the melt compounding, the maleic anhydride‐grafted polypropylene was used as compatibilizer which led to form an intercalated and/or exfoliated structure 9–12. However, few studies focused on polyethylene/organoclay nanocomposite samples have shown less degree of success in increasing interlayer d ‐spacing and structure development compared to the polypropylene‐based nanocomposites 13, 14…”
Section: Introductionmentioning
confidence: 99%
“…Thus, modified polymers having polar groups, called as compatibilizers or interfacial agents must be introduced in nanocomposite formulations to enhance the extent of intercalation as well as dispersion of organoclay in polyolefin matrix. In most research works carried out on polypropylene/organoclay nanocomposites prepared by the melt compounding, the maleic anhydride‐grafted polypropylene was used as compatibilizer which led to form an intercalated and/or exfoliated structure 9–12. However, few studies focused on polyethylene/organoclay nanocomposite samples have shown less degree of success in increasing interlayer d ‐spacing and structure development compared to the polypropylene‐based nanocomposites 13, 14…”
Section: Introductionmentioning
confidence: 99%